Thermal performance of graphene oxide nanofluid in microchannel heat exchanger - Ong, Y.S. (Begell House Inc., 2020)
Device miniaturization and complex work load due to rapid growth in technologies have imposed great challenges in aspects of thermal management to prevent overheating. Nanofluids are emerging as thermal solutions due to their enhanced thermal properties. Recently, graphene oxide (GO) nanofluids (NFs) has been studied and found to have high thermal conductivity. However, their potential in microchannel heat exchangers (MCHEs) remains unknown. This study aims to investigate the thermal performance of GO-NFs in MCHEs. GO nanoparticles were synthesized and confirmed using X-ray diffraction, whereas GO-NFs (0.02-0.1 wt.) were prepared and analyzed in terms of viscosity and thermal conductivity. The results showed that the minor addition of GO nanoparticles did not significantly affect the viscosity of GO-NFs, whereas the thermal conductivity was remarkably enhanced. This indicates that GO-NFs are very promising since they are able to improve the thermal performance of MCHEs with negligible impact on the pressure drop at low nanoparticle loading. The thermal performance of GO-NFs in MCHEs was investigated at different inlet flow rates (0.5-2 mL/min) and set temperatures (50-90Â°C). At a given set temperature, GO-NFs showed excellent thermal performance compared to water due to their higher thermal conductivity. Furthermore, GO-NFs showed better thermal performance at higher set temperatures due to their higher thermal conductivity at higher temperatures. This temperature-dependent thermal conductivity of GO-NFs is essential especially in applications involving higher temperatures. Furthermore, no clogging of GO nanoparticles in microchannels was observed at minor GO loadings (0.02-0.1 wt.). These results indicate that GO-NFs are very effective in heat transfer applications compared to water. Â© 2020 by Begell House, Inc.